EFFECT OF THE COMBINATION OF SALINITY AND WALNE FERTILIZER ON THE POPULATION GROWTH OF Nannochloropsis sp ON LABORATORY SCALE - Aslam, Atthoriq Habib Harry; Nasution, Syafruddin; Nurrachmi, Irvina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
ABSTRACT Activities of phytoplankton culture needed to be supported by physical and chemical parameters. This study aimed to analyze the effect of a combination of salinity and Walne fertilizer on the population growth of Nannochloropsis sp on the laboratory scale. The method used in this study is an experimental method using CRD (Completely Randomized Design) experimental design with 2 factors, namely salinity and Walne fertilizer, and each factor is given 3 levels of treatment. The level value of each factor is combined to obtain 9 combinations with 3 replications to obtain a total of 27 experimental units. The results of measuring the water quality parameters show that the media conditions were in good condition: an average temperature of 21℃, an average pH of 7.6, and the LED light used is ±2,000 lux. The results showed no significant effect of the combination of salinity and Walne fertilizer on the population growth of Nannochloropsis sp. The best combination value was obtained in the S1W1 treatment with a combination of 15 ppt salinity and 0.5 mL Walne fertilizer dose, resulting in cell population density (4125x103 cells/mL). The second best was obtained in the S1W2 combination with 15 ppt salinity and 1 mL Walne fertilizer dose (3775x103 cells/mL).